Broadband CrOCl Saturable Absorber with a Spectral Region Extension to 10.6 µm. Issue 2 (6th November 2019) - Wang, Mengxia; Zhang, Jian; Wang, Zhengping; Wang, Ci; van Smaalen, Sander; Xiao, Hang; Chen, Xi; Du, Chenlin; Xu, Xinguang; Tao, Xutang
Abstract: Nonlinear optical (NLO) materials with saturable absorption have attracted increasing attention because of their broad applications in the fields of optical communication, materials processing, biological detection, and surgery. However, their development is limited in the mid‐infrared (IR) range due to a lack of available materials with a wideband NLO response. Herein, the optical properties and applications of the transition metal oxychloride CrOCl, which has a broadband transparent region (0.8–18 µm) and a high laser damaged threshold, are studied. The saturable absorption of CrOCl is characterized at 1.06, 1.5, 2.0, 2.5, and 10.6 µm with nanosecond lasers by the Z‐scan method. With CrOCl as the saturable absorber (SA), passively Q‐switched solid‐state lasers are successfully realized at 1.06, 1.33, and 1.87 µm. This study is the first to report the use of a Cr 3+ material as an optical SA. The high transmittance and wideband NLO response of CrOCl indicate that CrOCl can be an excellent NLO IR material with extensive application potential in photonics. Abstract : The nonlinear optical properties and applications of CrOCl crystal, which has a broad transparent region (0.8–18 µm), are demonstrated for the first time. Its saturable absorption property is characterized from 1.06 to 10.6 µm. With CrOCl as the saturable absorber (SA), the passively Q‐switched operations are realized for 1.06, 1.33 and 1.87 µm solid‐state lasers.